Marcas ensaísticas no cinema de Julio Bressane - Marcone de Souza Faria (2023)
Essay marks in the cinema of Julio Bressane aims to discuss the concept of film-essay and how it is present in the work of the Brazilian filmmaker, particularly in some of his films. The concept of the essay and the film-essay will be defined and discussed based on a set of critical and theoretical texts. We will discuss the essayistic potential of Bressane's cinema, and how the filmmaker uses the cinematographic device as a hermeneutic instrument. The text aims to understand the multiplicity and creativity of Bressane's films from the perspective of the filmic essay, and how this perspective can help the spectator to have a more open and rich contact with his work, in this cinema that thinks and makes you think.